2012
DOI: 10.4028/www.scientific.net/amm.226-228.444
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Sound Quality for Car Compressor

Abstract: As cars become more and more quiet the sound quality of rotary components such as car compressor becomes more important in the customer’s subjective perception of passenger car quality. This needs a new evaluation method which is not only the traditional method like sound pressure level but also Psychoacoustic Metrics to focus the specification of component sounds. This paper on one hand analyzed one car’s abnormal noise reason through the tests, found the main problem frequency band of the compressor, and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Zhuang and Zuo (2014), who focused also on car interior sound quality, found that sound quality was better than sound pressure and that sound sharpness was more disturbing than volume. Hou, Han, and Xu (2012) used psychoacoustic metrics instead of conventional interior sound measuring methods, which they believed fell short of evaluating interior sound quality. They specified the frequency bands of the car compressor.…”
Section: Research On Quality In the Automotive Industrymentioning
confidence: 99%
“…Zhuang and Zuo (2014), who focused also on car interior sound quality, found that sound quality was better than sound pressure and that sound sharpness was more disturbing than volume. Hou, Han, and Xu (2012) used psychoacoustic metrics instead of conventional interior sound measuring methods, which they believed fell short of evaluating interior sound quality. They specified the frequency bands of the car compressor.…”
Section: Research On Quality In the Automotive Industrymentioning
confidence: 99%